Potential impacts of climate change on food crops in the state of Piauí, Brazil - Sousa e Silva, Laila Lucia; Siqueira Tavares Fernandes, Gabriel; de Araujo Lima, Edivania; Almeida Lopes, Jessica Rafaelly; de Moura Neto, Arão; de Oliveira Silva, Raiany (Revista Ceres, 2024)
Climate change has made food security vulnerable. Therefore, it is important to have discussions on the subject and take actions that minimize the environmental impacts on family farming, that will be directly or indirectly affected by climatic events. With this in mind, this study aimed to identify climate changes in the state of Piauí based on climate projections and to verify their possible impacts on the suitability of growing food crops, such as beans, corn, cassava, and cashew. The climate scenarios analyzed were 2011–2040, 2041–2070, and 2071–2100. The observed data on current climate came from the National Institute of Meteorology (INMET), and future climate projections came from the Brazilian Portal of Climate Projections of the National Institute for Space Research (INPE). Based on the climatic data obtained (current and future), the climatological water balance was calculated, using the method proposed by Thorntwaite, with consecutive characterization of the suitability for crops. All maps were generated in QGIS. According to the results, crops that may suffer from water deficit are beans and cashews. The latter, in the RCP 8.5 scenario (2071–2100) shows unsuitability for cultivation throughout the state. The population with the highest rate of social vulnerability is the one that will be most damaged by the events caused by climate change.